RPE cell and sheet properties in normal and diseased eyes - Rashid, Alia (2016)
Previous studies of human retinal pigment epithelium (RPE) morphology found spatial differences in density: a high density of cells in the macula, decreasing peripherally. Because the RPE sheet is not perfectly regular, we anticipate that there will be differences between conditions and when and where damage is most likely to begin. The purpose of this study is to establish relationships among RPE morphometrics in age, cell location, and disease of normal human and AMD eyes that highlight irregularities reflecting damage. Cadaveric eyes from 11 normal and 3 age-related macular degeneration (AMD) human donors ranging from 29 to 82 years of age were used. Borders of RPE cells were identified with phalloidin. RPE segmentation and analysis were conducted with CellProfiler. Exploration of spatial point patterns was conducted using the “spatstat” package of R. In the normal human eye, with increasing age, cell size increased, and cells lost their regular hexagonal shape. Cell density was higher in the macula versus periphery. AMD resulted in greater variability in size and shape of the RPE cell. Spatial point analysis revealed an ordered distribution of cells in normal and high spatial disorder in AMD eyes. Morphometrics of the RPE cell readily discriminate among young vs. old and normal vs. diseased in the human eye. The normal RPE sheet is organized in a regular array of cells, but AMD exhibited strong spatial irregularity. These findings reflect on the robust recovery of the RPE sheet after wounding and the circumstances under which it cannot recover.